The Effect Of Micro Wave Diathermy And Core Stability Exercise On Pain In Low Back Pain Myogenic Patients At RSUD Rantauprapat - Irmayani .; Sri Melda Bangun; Anggi Isnani Parinduri; Rosita Ginting; Wahyu Hidayat (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
The most common musculoskeletal complaint encountered throughout human life is Low Back Pain (LBP) which causes very long inflammatory pain and causes functional limitations of myogenic LBP which can cause muscle spasms that can cause sufferers to feel pain. Muscle atrophy for a long time causes a decrease in muscle strength that can occur in patients with myogenic LBP. This study is a quantitative study with a quasi-experimental approach using a pretest posttest one group design which aims to explain the effect of giving MWD and CSE on reducing pain in Myiogenic LBP in Physiotherapy Poly Hospital Rantauprapat. The population in this study were all LBP patients who visited Rantauprapat Hospital with a sample of 18 myogenic LBP patients who were drawn using purposive sampling based on predetermined criteria. Data were collected using primary and secondary data. The results showed that the average pain complaint before MWD and CSE was 5.90 and after MWD and CSE interventions were given, the average pain was 3.30. The pain felt by the patient after the intervention was initially average in the moderate pain category to mild pain. The results also showed that there was an effect of giving MWD and CSE on reducing myogenic LBP pain with p = 0.000. It is hoped that it can be used as material for policy making in improving health services, especially MWD and CSE physiotherapy services.